Peningkatan Pertumbuhan dan Hasil Sawi Hijau (Brassica chinensis) oleh Bakteri Fotosintetik dalam Kondisi Lapangan - Avianto, Yovi (Universitas Pembangunan Nasional Veteran Yogayakarta, 2023)
In the 21st century, there has been a gradual shift in agricultural practices towards embracing organic concepts and harnessing the potential of beneficial bacteria to amplify crop production. Simultaneously, there is a heightened public awareness concerning the significance of integrating leafy vegetables into diets. A promising avenue to address these evolving concerns involves the adoption of photosynthetic bacteria as biofertilizers. This study sought to examine the extent to which pak choy plant yield is enhanced through the supplementation of photosynthetic bacteria (PSB). Furthermore, the investigation aimed to elucidate the underlying mechanisms by which photosynthetic bacteria contribute to the growth of mustard green plants and determine the optimal PSB dosage to achieve maximal production. Conducted between November and December 2022 at the Biotech Botanical Garden, the research employed a complete randomized block design incorporating various PSB treatment levels, including no PSB spray, a 10 mL/L dosage, a 50 mL/L dosage, and a 100 mL/L dosage. An array of growth indicators such as plant height, leaf count, leaf width, root length, fresh and dry shoot weight, fresh and dry root weight, relative water content, and consumption index, were meticulously observed. The study revealed noteworthy alterations in improved growth and yield (consumption index). The optimal PSB dosage, identified to maximize pak choy plant production, was determined to be 67.25 mL/L.